Epistemologi Ilmu Munasabah Al-Quran - Abdul Rohman (Bayani, 2022)
The science of mun?sabah al-Quran requires a correlation between one verse or one letter with another verse or letter and strives to make all the verses of the Qur'an into a unified whole. This paper discusses the epistemology of the science of mun?sabah al-Quran. The purpose of this paper is to find out how knowledge of mun?sabah science can be obtained, from which sources, and how the methods and what the rules of mun?sabah science are like in the Koran. The method used is descriptive analysis with a qualitative approach based on library research studies. The results obtained are that the knowledge of mun?sabah is obtained through deep reflection from an interpreter; the source is the creative mind and ijtihad of a commentator; There are four methods to reveal the munasabah side of the Koran and there are three rules that apply to understanding a verse or letter in the Koran to reveal the correlation side.